Analisis Tindak Tutur Ilokusi Dalam Film Pendek “Capciptop! (2020)” Pada Kanal Youtube Ravacana Films (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to determine (1) the types of illocutionary speech acts in the short film "CAPCIPTOP! (2020)"; and (2) how the purpose of the speech in the short film "CAPCIPTOP! (2020)". The researcher used descriptive qualitative research. The data source used in this research is the dialog in the short film "CAPCIPTOP! (2020)" which is unique and closely related to the habits of Indonesian society. Data collection in this study used the technique of free listening and note taking. The data in this study are in the form of speech quotations that show illocutionary speech acts. The results of the data obtained are analyzed descriptively qualitative. It can be concluded that the forms of speech acts contained in the short film "CAPCIPTOP! (2020)" are assertive, directive, commissive, expressive, and declarative.